Significance of Mutation Spots and Concurrent Gene Mutations on Prognosis and Clinical Outcomes in Myelodysplastic Syndromes With SF3B1 Mutation - Qi Liu; Fanhuan Xu; Juan Guo; Feng Xu; Xinhui Huang; Jianan Chen; Jiacheng Jin; Liyu Zhou; Qi He; Dong Wu; Luxi Song; Zheng Zhang; et al. (Cancer Medicine, 2025)
ABSTRACT Purpose To investigate the clinical characteristics and prognosis of mutation spots and concomitant gene mutations in myelodysplastic syndromes (MDS) with SF3B1 mutation (SF3B1mut). Patients and Methods Patients diagnosed with MDS at Shanghai Jiao Tong University School of Medicine Affiliated Sixth People's Hospital from October 2008 to November 2023 were enrolled in this study. SF3B1mut was identified by next‐generation sequencing (NGS). Results One hundred and seven (8.7%) cases harbored the SF3B1 mutation. The most frequent SF3B1mut, noted in 47.66% of all patients, was the hotspot K700E. K666 and R625 were observed in 24.30% and 9.35%, respectively. Two less frequent mutation subtypes accounted for 5.61% of H662 and 4.67% of E622. Patients with the K666 mutation showed more severe thrombocytopenia (p = 0.032), significantly lower NK cell percentage (p = 0.001), and the Th1/Th2 ratio (p = 0.018) in the bone marrow (BM). The overall survival (OS) in patients with E622 and H662 mutations was significantly longer than that of patients with the R625 mutation (p = 0.045) and the K666 mutation (p = 0.010). Multi‐variance analysis showed the SF3B1 mutation involving the K666 hotspot independently predicted overall survival in MDS (HR 2.094, p = 0.050). Notably, most (11/13, 84.6%) of concomitant TP53 mutations were mono‐hit, which did not affect the survival of patients in our cohort. Conclusions SF3B1mut patients with specific mutation spots and concomitant gene mutations showed distinct clinical features and prognosis. Consequently, a comprehensive study of specific subtypes is of great significance for improving the prognosis of patients with SF3B1 mutations.